Cultural history - Chartier, Roger (New York Polity Press, 1993)
Chartier examines various approaches to the history of cultural forms, including the work of the Annales tradition, the contributions of Foucault and Elias, and the more recent writings of Robert Darnton, Carlo Ginzburg and others. The second part of the volume offers a series of case studies. Chartier explores, among other things, the cultural significance of symbolic role reversals, the representations of peasant reading practices in the Age of Enlightenment, and the role of intellectuals in the universities and labour markets of early modern Europe. Through these case studies Chartier elaborates the elements of a highly original approach to the history of cultural forms.